TEOLOGI SAKIT DAN KEMATIAN DI MASA PANDEMIC COVID-19 : Studi Pengaruh Spritualitas, Alkitab, Gereja, Dukungan Sosial, dan Media Sosia - Keloso S. Ugak; Hendra; Ranni Christina Nafensy (Jurnal Teologi Pambelum, 2022)
The purpose of the study was to identify the factors that influence the theological understanding of the Evangelical Kalimantan Church (GKE) about illness and death infected with COVID-19 and to find a formulation of the theological style of illness and death amid the COVID-19 pandemic for GKE. The study was conducted to determine and analyze the influence of spirituality (X1), the Bible (X2), the church (X3), social support (X4), and social media (X5) as exogenous variables on the theology of sickness and death (Y) as endogenous variables. The object of research is the congregations of GKE Eppata Banjarmasin, Eben Ezer Banjarmasin, Palangka Raya, Banjarbaru, and Tamiang Layang. This type of research is explanatory research with a quantitative approach. Primary data collection using online questionnaires and limited interviews is done. The research respondents were 89 congregations that were identified as infected with Covid-19. Data analysis techniques to determine the effect of exogenous variables X1, X2, X3, X4 & X2 on endogenous variables (Y) using the Partial Least Square (PLS) analysis technique with SmartPLS 3.0 software. The study results concluded that social media (X5) positively and significantly affected the theology of sickness and death (Y). Other findings show that there is a positive but not significant effect on the variables "spirituality" (X1), "church" (X3), and "social support" (X4) on the theology of sickness and death (Y). Furthermore, finally, there is a negative and insignificant effect of the Bible variable (X2) on the theology of sickness and death (Y).